Impacts of Future Climate Change on the Southern Canadian Prairies: A Paleoenvironmental Perspective - Lemmen, D. S.; Vance, R. E.; Wolfe, S. A.; Last, W. M. (Geoscience Canada, 1997)
Water and soil are critical to the prosperity of the southern Canadian prairies. Both have been strongly influenced by historic climate variability, and by even more significant climate changes that have occurred during the Holocene. These observations, together with general circulation model projections of increasing aridity in this region, raise concerns about the potential impacts of future climate change. Collaborative, multidisciplinary research conducted over the past five years as part of the Palliser Triangle Global Change Project has focussed on geoscientific aspects of climate change in the driest portion of the Canadian prairie provinces. Re-construction of past climates, based on multiple paleolimnological indicators (plantmacrofossils, diatoms, ostracodes, algal pigments, sedimentology, mineralogy, and stable isotope geochemistry), demonstrates that the historic record of roughly 100 years does not adequately capture the range of climatic variability observed during even the last 2000 years. The response of hydrologic and geomorphic systems to past changes in climate documents a surprisingly dynamic landscape.The best analogues for projected future climates feature a regional water table more than 4 m below its present level and enhanced wind erosion. The paleoenvironmental record highlights the susceptibility of water and soil resources to climate-induced impacts that are likely to adversely affect human activities in the region over the next century. Résumé L’eau et le sol constituent deux éléments essentiels à la prospérité des régions de la portion sud des plaines canadiennes. Ces deux éléments ont été grandement affectés par les fluctuations climatiques de la période historique ainsi que par les fluctuations encore plus importantes durant l’Holocène. Ces observations ajoutées aux projections d’un accroissement de l’aridité dans la région à partir de modèle de la circulation atmosphérique générale soulèvent l’inquiétude quant aux effets possibles de changements climatiques à venir. Les recherches multidisciplinaires conjuguées effectuées au cours des derniers cinq ans dans le cadre du Projet des changements à l’échelle du globe dans le triangle de Palliser ont été concentrées sur sur les aspects géoscientifiques des changements climatiques de la portion la plus aride des prairies canadiennes. La reconstitution des climats d’autrefois basée sur une gamme d’indicateurs paléolimnologiques (macrofossiles de plantes, diatomées, ostracodes, pigments algaires, données sédimentologiques, minéralogiques et de géochimie d’isotopes stables) montrent que le registre des variations d’une centaine d’années n’est pas suffisamment étendu pour montrer toute fourchette des variations climatiques relevées pour la période des derniers 2000 ans. Les données accumulées montrent que la réponse des systèmes hydrologiques et géomorphologiques aux changements climatiques entraînent des changements de paysage plus importants que prévus. Les meilleurs modèles de prévision climatiques indiquent un abaissement du niveau régional de la nappe phréatique de 4 m et une augmentation de l’érosion éolienne. Les données paléoenvironnementales montrent que l’eau et le sol sont des ressources particulièrement sensibles aux effets de changements climatiques et que cela nuira grandement aux activités humaines de cette région au cours du prochain siècle.